2017
DOI: 10.1007/s00280-017-3479-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of panitumumab in a patient with chronic kidney disease

Abstract: PurposeData on panitumumab dosing in cancer patients with renal insufficiency are lacking. Here, we report a 63-year-old metastatic colorectal cancer patient with chronic kidney injury with a glomerular filtration rate of approximately 11 mL/min.MethodsPharmacokinetic parameters, including dose-normalized area under the curve, clearance and elimination half-life (T 1/2) after the 11th and 12th infusions were estimated using trapezoidal non-compartmental methods. Data were compared to previous reported pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…However, our findings are limited to a small number of CKD model rats investigated herein. The clearance of other antibody drugs (bevacizumab and panitumumab) was similar between the subjects with normal renal function and patients with end-stage renal disease (Garnier-Viougeat et al, 2007;Krens et al, 2018). The difference in the outcomes between the present study and that from the previous study could be attributed to the presence of different types of CKD etiology or pathophysiology, such as the patients with end-stage renal disease undergoing hemodialysis being anuric.…”
Section: Discussioncontrasting
confidence: 53%
“…However, our findings are limited to a small number of CKD model rats investigated herein. The clearance of other antibody drugs (bevacizumab and panitumumab) was similar between the subjects with normal renal function and patients with end-stage renal disease (Garnier-Viougeat et al, 2007;Krens et al, 2018). The difference in the outcomes between the present study and that from the previous study could be attributed to the presence of different types of CKD etiology or pathophysiology, such as the patients with end-stage renal disease undergoing hemodialysis being anuric.…”
Section: Discussioncontrasting
confidence: 53%
“…By comparison, panitumumab is administered by weight at a dose of 6 mg/kg every 2 weeks; a 60-min infusion time is recommended for total doses ≤ 1,000 mg, and a 90-min infusion time is recommended for total doses > 1,000 mg (7). At this administration schedule, panitumumab's mean half-life is 7.5 days, with a minimum recorded mean serum concentration of 39 μg/mL (18). Studies have indicated that it takes 3 infusions of panitumumab to reach steady state (19), although similar information has not been published for cetuximab.…”
Section: Mode Of Action Against Egfrmentioning
confidence: 99%
“…A reference line at y = 0 and local regression smoother trend lines have been included. Panels from the left: ETA3 versus body weight in kg (WT), ETA3 versus ALT concentration in U/L (AST), ETA3 versus AST concentration in U/L (ALT), and ETA3 versus creatinine clearance in mL/min (CL CR ) [11] showed that serum concentrations of panitumumab were within the ranges presented here for renal function subgroups. The patient's CL CR was 11 mL/min (severely impaired renal function); C max was 125 µg/mL (after the 11th and 12th infusions) and C trough was 37 µg/mL (just before the 12th infusion).…”
Section: Discussionmentioning
confidence: 64%
“…Here, we present data from three open-label phase 2 and phase 3 studies in patients with mCRC (NCT00083616, NCT00089635, and NCT00113763) to assess the effect of hepatic and renal impairment on exposure to panitumumab. Additionally, these results are comprehensively evaluated together with the limited real-world evidence available for the pharmacokinetics of panitumumab in patients with mCRC and severe hepatic or renal dysfunction, which is a rare patient population to study [ 11 , 12 ]. The objective of this manuscript was to provide observed panitumumab pharmacokinetics data from mCRC patients with mild-to-moderate hepatic dysfunction and mild-to-moderate renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%